GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI VITAMIN C MAHASISWA D-III FARMASI STIKES WIDYA DHARMA HUSADA TANGERANG PADA PANDEMI COVID-19 TAHUN 2022 - Dwi Krisiyowati, Anis (Jurnal Farmasi (Journal of Pharmacy), 2023)
Vitamin C is an essential water-soluble vitamin that is widely used as a body supplement. Misuse of the dosage will cause unwanted side effects such as nausea vomiting, diarrhea, increasing the risk of diabetes. This study is to find out an overview of the level of knowledge on self-medicating the use of vitamin C for D III Pharmacy students of STIKes Widya Dharma Husada Tangerang during the Covid-19 pandemic. This study is a descriptive study with 96 respondents taken by the cross- sectional method. Data were obtained through questionnaires and analyzed using percentages. The results obtained in this study are the characteristics of respondents based on age Most of them are found at the age of 17-25 years, namely 87.5%, based on gender Most of them are found in women, namely 84.37%, based on work more than half of them are found in those who are not working, namely 52.08%, and based on a history of exposure to covid-19 more than half of them are found in those who have been exposed to covid-19, namely 73.96%, while the characteristics of respondents' knowledge about the use of well-informed vitamin C were highest based on the age of 17-25 years as much as 84.37%, in the female sex as much as 81.25%, in unemployed work as much as 50%, in the history of exposure to covid-19 who had been exposed to covid-19 as much as 70.83%. Conclusion: The results of this study show that the concentration of the level of knowledge on self-medicating the use of vitamin C for D III Pharmacy students of STIKes Widya Dharma Husada Tangerang during the Covid-19 pandemic was 96.88% included in the "Good" category.